PENGUATAN KUALITAS PRODUKSI DAN PENGEMASAN TEMPE DI BATU TUMBUH JATIWARINGIN BEKASI - Sugeng Santoso; Catarina Cori (Lembanga Pengabdian Masyarakat, 2023)
The activity was carried out in the Jaticempaka Village, Pondok Gede District, Bekasi City, West Java Province. This activity aims to find out the process of making tempeh and then provide reinforcement regarding the quality of production and packaging of tempe through outreach to craftsmen and employees of tempe making. The material provided is to provide information about cleanliness that must always be considered and attractive packaging of tempe so that tempe is liked by all groups and tempe remains the pride of Indonesia's global food.